Gene Expression Modification by an Autosomal Inversion Associated With Three Male Mating Morphs - Loveland, Jasmine L.; Lank, David B.; Küpper, Clemens (Frontiers in Genetics, 2021)
Chromosomal inversions are structural rearrangements that frequently provide genomic substrate for phenotypic diversity. In the ruff Philomachus pugnax, three distinct male reproductive morphs (Independents, Satellites and Faeders) are genetically determined by a 4.5 Mb autosomal inversion. Here we test how this stable inversion polymorphism affects gene expression in males during the lekking season. Gene expression may be altered through disruptions at the breakpoints and the accumulation of mutations due to suppressed recombination. We used quantitative PCR to measure expression of 11 candidate inversion genes across three different tissues (liver, adrenal glands and gonads) and tested for allelic imbalance in four inversion genes across 12 males of all three morphs (8 Independents, 2 Satellites, 2 Faeders). We quantified CENPN transcripts, an essential gene disrupted by the inversion at the proximal breakpoint, at different exons distributed near and across the breakpoint region. Consistent with dosage dependent gene expression for the breakpoint gene CENPN, we found that expression in Independents was broadly similar for transcripts segments from inside and outside the inversion regions, whereas for Satellites and Faeders, transcript segments outside of the inversion showed at least two-fold higher expression than those spanning over the breakpoint. Within the inversion, observed expression differences for inversion males across all four genes with allele-specific primers were consistent with allelic imbalance. We further analyzed gonadal expression of two inversion genes, HSD17B2 and SDR42E1, along with 12 non-inversion genes related to steroid metabolism and signaling in 25 males (13 Independents, 7 Satellites, 5 Faeders). Although we did not find clear morph differentiation for many individual genes, all three morphs could be separated based on gene expression differences when using linear discriminant analysis (LDA), regardless of genomic location (i.e. inside or outside of the inversion). This was robust to the removal of genes with the highest loadings. Pairwise correlations in the expression of genes showed significant correlations for 9–18 pairs of genes within morphs. However, between morphs, we only found a single association between genes SDR42E1 and AROM for Independents and Satellites. Our results suggest complex and wide-ranging changes in gene expression caused by structural variants.